Immunological Factors in Recurrent Pregnancy Loss: Mechanisms, Controversies, and Emerging Therapies - Efthalia Moustakli; Anastasios Potiris; Athanasios Zikopoulos; Eirini Drakaki; Ioannis Arkoulis; Charikleia Skentou; Ioannis Tsakiridis; Themistoklis Dagklis; Peter Drakakis; Sofoklis Stavros (Biology)
Immunological factors have gained growing recognition as key contributors to recurrent pregnancy loss (RPL) after in vitro fertilization (IVF), representing a major challenge in reproductive medicine. RPL affects approximately 1–2% of women trying to conceive naturally and up to 10–15% of those undergoing IVF, where overall success rates remain around 30–40% per cycle. An imbalance in maternal immunological tolerance toward the semi-allogeneic fetus during pregnancy may lead to miscarriage and implantation failure. IVF-related ovarian stimulation and embryo modification offer additional immunological complications that can exacerbate existing immune dysregulation. Recent advances in reproductive immunology have significantly deepened our understanding of the immune mechanisms underlying RPL following IVF, particularly highlighting the roles of regulatory T cells (T regs), natural killer cells, cytokine dysregulation, and disruptions in maternal–fetal immune tolerance. In order to better customize therapies, this evaluation incorporates recently discovered immunological biomarkers and groups patients according to unique immune profiles. Beyond conventional treatments like intralipid therapy and intravenous immunoglobulin, it also examines new immunomodulatory medications that target certain immune pathways, such as precision immunotherapies and novel cytokine modulators. We also discuss the debates over immunological diagnostics and therapies, such as intralipid therapy, intravenous immunoglobulin, corticosteroids, and anticoagulants. The heterogeneity of patient immune profiles combined with a lack of strong evidence highlights the imperative for precision medicine to improve therapeutic consistency. Novel indicators for tailored immunotherapy and emerging treatments that target particular immune pathways have encouraging opportunities to increase pregnancy success rates. Improving management approaches requires that future research prioritize large-scale clinical trials and the development of standardized immunological assessments. This review addresses the immunological factors in RPL during IVF, emphasizing underlying mechanisms, ongoing controversies, and novel therapeutic approaches to inform researchers and clinicians.